(untitled) (Jurnal Bina Praja, 2018)
Medical treatment and nutrition improvement may extend the life of human beings. This brings out a wider working opportunity to be productive. Therefore, ASN (Aparatur Sipil Negara) performance prior to near retirement should be better. Prior to retirement will always be a burden and it is not a productive moment. Knowing this phase deeply will lead to making a policy of retirement for ASN in dealing with their retirement. Their performance at this phase sometimes causes them to get less attention by superior or their peers; they think of ASN at this phase to be less productive and just waiting for the retirement to come. The aim of this research was to find a management model for the civil servant in approaching the retirement (near-retirement phase). The retirement period experienced by each person after the end of his/her working period is expected to be comfortable. The research utilizes a case study design with a qualitative approach. The interview was conducted in-depth (in-depth interview) in which the informants were the civil servants in the Regional Secretariat of Pemalang District. The data credibility was carried out by using data triangulation. The findings of this research indicated that the internal social relationship of male employees toward retirement was more active than female employees. Moreover, male employees cared more about health factors than female employees. Male employees took more time before retirement whereas female employees were more relaxed. In addition, they need social supports on the eve of retirements such as financial preparation, role adjustment, and retirement activities. Family and colleague’s supports were the most important supports needed before retirement.